Influence of environmental factors and tributaries on toxic cyanobacterial growth - Natalia Herrera; Susana Llano; Gustavo Peñuela (PLoS ONE, 2026)
Toxic cyanobacteria are widely present in water bodies worldwide, particularly in reservoirs. The Calima Reservoir is primarily used for energy generation, but some areas of it are also designated for recreational activities, making it a significant contributor to regional and national tourism. In this study, four sampling events were conducted in 2023, covering different seasonal periods. During these samplings, various species of potentially toxic cyanobacteria were detected; the presence of these cyanobacteria was analyzed in relation to several physicochemical variables, and microcystin‑LR (MC-LR) was detected in four of the six sampling stations, although in concentrations below the maximum permissible limit. The reservoir’s temperature showed a positive correlation with cyanobacterial abundance. One of the objectives of the research was to assess the growth of M. aeruginosa by exposing it to water samples from four tributaries that flow directly into the reservoir, each with distinct physicochemical properties. The highest growth induction, exceeding 400%, was observed in samples from Tributary 2 (T2), located at the center of the reservoir. The analysis revealed that the variables most significantly associated with enhanced M. aeruginosa proliferation were ammoniacal nitrogen (32.8 mg NH 3 -N/L), alkalinity (280 mg CaCO 3 ), and Kjeldahl nitrogen (33.6 mg N/L). In contrast, negative associations were observed with indicators of biodegradable organic matter, including of biochemical oxygen demand (BOD), chemical oxygen demand (COD), total organic carbon (TOC) and coliform-type microorganisms, indicating an environment conducive to the proliferation of M. aeruginosa . These findings suggest that it is important to conduct detailed analyses of tributary waters to identify areas with high potential for cyanobacterial blooms. These findings highlight the influence of external nutrient inputs on bloom formation and the need for focused mitigation to protect water quality.